Transverse testicular ectopia with persistent Mullerian duct syndrome: Report and review of two cases. (10th November 2022) - Yang, Min; Lin, Xiaobin; Liu, Zhijun; Zhang, Peijian; Xiao, Wang; Chen, Yingchun; Chen, Yiyi; Zhuang, Yangmu; Zheng, Lian; Duan, Shouxing
Abstract: Transverse testicular ectopia is a rare anomaly characterized by both testes descending through a single inguinal canal. The objective of this study was to investigate the pathogenesis, diagnosis, and treatment of transverse testicular ectopia (TTE) with persistent Mullerian duct syndrome (PMDS), and to deepen the understanding of the disease in clinical. A retrospective analysis of the clinical manifestation, diagnosis, and treatment of two children suffering from TTE with PMDS was conducted. Previous studies on the characteristics, diagnosis, and treatment of this disease were reviewed. The two patients were treated with laparoscopy‐assisted transseptal orchidopexy‐inguinal evaluation. After the surgery, the two patients recovered well. The follow‐up visits were done 3 months after the operation. An ultrasound examination confirmed that the two patients had testes in the orthotopic position and normal size. TTE with PMDS is an exceedingly rare disease. The patients manifested cryptorchidism on one side; contralateral inguinal hernia was suspected. Detailed physical and ultrasound examinations before the operation are the key to the early diagnosis of TTE. Laparoscopic evaluation is helpful for the diagnosis and finding of other abnormalities. Surgical treatment is the only method to cure the disease; long‐term follow‐up is needed after TTE operation.